When the body is past fixing: caring for bodies, caring for people. Issue 5 (15th October 2013) - Melia, Kath M
<x xml:space="preserve">Abstract</x> Aims and objectives To discuss the social context within which end‐of‐life nursing care takes place and to consider palliative options of last resort and the differences between societal and professional views on these. Background The distinction between life and death is not so straightforward as was once the case. Resuscitation and the increasing capability of intensive care to 'save' patients have implications for nursing practice in a society where there is an increasing demand that individuals should be able to choose the time of their death. Methods This is a discursive paper. Conclusions There are differences between the professional view on end‐of‐life options and the societal debates calling for a more libertarian approach. The problem for professionals is that the call for choice of the individual involves a different approach to end‐of‐life care, an approach that does not sit well with current professional ethics. One way forward might be a gradual reconsidering of what end‐of‐life care might reasonably encompass. Relevance to clinical practice Nurses are the healthcare workers who have the most prolonged and intimate contact with bodies. The way in which we conceptualise the body is central to much of the work carried out in the transition between life and death and is an important part of nursing.